Rationale and Means to Target Pro-Inflammatory Interleukin-8 (CXCL8) Signaling in Cancer - Laura M. Campbell; Pamela J. Maxwell; David J.J. Waugh (MDPI AG, 2013)
It is well established that chronic inflammation underpins the development of a number of human cancers, with pro-inflammatory signaling within the tumor microenvironment contributing to tumor progression and metastasis. CXCL8 is an ELR+ pro-inflammatory CXC-chemokine which mediates its effects via signaling through two G protein-coupled receptors, CXCR1 and CXCR2. Elevated CXCL8-CXCR1/2 signaling within the tumor microenvironment of numerous cancers is known to enhance tumor progression via activation of signaling pathways promoting proliferation, angiogenesis, migration, invasion and cell survival. This review provides an overview of established roles of CXCL8-CXCR1/2 signaling in cancer and subsequently, discusses the possible strategies of targeting CXCL8-CXCR1/2 signaling in cancer, covering indirect strategies (e.g., anti-inflammatories, NFκB inhibitors) and direct CXCL8 or CXCR1/2 inhibition (e.g., neutralizing antibodies, small molecule receptor antagonists, pepducin inhibitors and siRNA strategies). Reports of pre-clinical cancer studies and clinical trials using CXCL8-CXCR1/2-targeting strategies for the treatment of inflammatory diseases will be discussed. The future translational opportunities for use of such agents in oncology will be discussed, with emphasis on exploitation in stratified populations.